Accounting Quality, Stock Price Delay, and Future Stock Returns* - Callen, Jeffrey L.; Khan, Mozaffar; Lu, Hai (Contemporary Accounting Research, 2013)
In frictionless capital markets with complete information and rational investors, stock prices adjust to new information instantaneously and completely. However, a substantial body of research studies information imperfections such as asymmetric information and incomplete information. Information imperfections potentially hinder timely price discovery and are likely associated with delayed stock price adjustment to information. Our first research question therefore is whether the quality of accounting information (or “accounting quality”) is one such information imperfection that is associated with cross‐sectional variation in stock price delay. We define accounting quality as the precision with which financial reports convey information to equity investors about the firm’s expected cash flows. Poor accounting quality is likely associated with higher expected returns through uncertainty about stock valuation parameters and incomplete information. Our second research question therefore is whether the accounting quality component of price delay is associated with higher future stock returns. Consistent with our hypotheses, the results show that poor accounting quality is associated with delayed price adjustment and higher future stock returns. Thus, accounting quality plays a role in timely stock price discovery.